1989
DOI: 10.1007/bf00291041
|View full text |Cite
|
Sign up to set email alerts
|

A non-radioactive in situ hybridization method for the localization of specific RNAs in Drosophila embryos reveals translational control of the segmentation gene hunchback

Abstract: We have developed a non-radioactive in situ hybridization technique for the localization of RNA in whole mount Drosophila embryos. After fixation, whole embryos are hybridized in situ with a DNA probe which has been labeled with digoxygenin. The hybridization products are detected by using a phosphatase-coupled antibody against digoxygenin. In parallel experiments, embryos can be treated with an antibody directed against the corresponding protein product to allow the detection of its distribution using standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1,246
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,485 publications
(1,261 citation statements)
references
References 23 publications
2
1,246
1
Order By: Relevance
“…In Drosophila, eight such proteins are known. Six of these proteins are involved in patterning the early embryo and directing morphogenesis (including Bicoid, Torso, Toll, Nanos, Hunchback, and Caudal; Driever and Nusslein-Volhard, 1988;Casanova and Struhl, 1989;Tautz and Pfeifle, 1989;Gay and Keith, 1992;Wang et al, 1994;Dubnau and Struhl, 1996). The remaining two proteins known to be translated upon egg activation in Drosophila are Smaug (Smg), which plays a major role in the degradation of maternal transcripts (see below; Dahanukar et al, 1999;Tadros et al, 2007) and the Cdc25 homolog String, which activates MPF and is thus important for the rapid nuclear divisions that occur during early embryogenesis (Spradling, 1993).…”
Section: Maternal Transcript Translationmentioning
confidence: 99%
“…In Drosophila, eight such proteins are known. Six of these proteins are involved in patterning the early embryo and directing morphogenesis (including Bicoid, Torso, Toll, Nanos, Hunchback, and Caudal; Driever and Nusslein-Volhard, 1988;Casanova and Struhl, 1989;Tautz and Pfeifle, 1989;Gay and Keith, 1992;Wang et al, 1994;Dubnau and Struhl, 1996). The remaining two proteins known to be translated upon egg activation in Drosophila are Smaug (Smg), which plays a major role in the degradation of maternal transcripts (see below; Dahanukar et al, 1999;Tadros et al, 2007) and the Cdc25 homolog String, which activates MPF and is thus important for the rapid nuclear divisions that occur during early embryogenesis (Spradling, 1993).…”
Section: Maternal Transcript Translationmentioning
confidence: 99%
“…In situ hybridizations were done using digoxygenin-11-dUTP-labeled DNA probes (Boehringer-Manheim) according to Tautz and Pfeifle (1989), with the following modification. We found that reducing the probe size to <200 bp was necessary to reduce background staining.…”
Section: In Situ Hybridizationsmentioning
confidence: 99%
“…The yield of in vitro transcription was estimated in a spot test (protocol according to Roche Nonradioactive In Situ Hybridization Manual). The RNA in situ procedure (Tautz and Pfeifle 1989) was adapted for alkaline phosphatase revelation (see: http://www.fruitfly.org/about/methods/ RNAinsitu.html). Anti-Digoxigenin-AP Fab fragments (Roche) were used to detect the probes, and Vectastain® Elite was applied for diaminobenzidine reaction.…”
Section: In Situ Hybridization and Immunostainingmentioning
confidence: 99%